2000
DOI: 10.1016/s0092-8674(00)80850-8
|View full text |Cite
|
Sign up to set email alerts
|

Tim23 Links the Inner and Outer Mitochondrial Membranes

Abstract: Tim23, a key component of the mitochondrial preprotein translocase, is anchored in the inner membrane by its C-terminal domain and exposes an intermediate domain in the intermembrane space that functions as a presequence receptor. We show that the N-terminal domain of Tim23 is exposed on the surface of the outer membrane. The two-membrane-spanning topology of Tim23 is a novel characteristic in membrane biology. By the simultaneous integration into two membranes, Tim23 forms contacts between the outer and inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 40 publications
9
137
0
Order By: Relevance
“…6a). Surprisingly, it has been reported that Tim23 is integrated into the outer membrane through its N-terminal domain 25 . Therefore, we investigated which domain of Tim23 forms the cation-selective channel identified here.…”
Section: Channel Formation By the C-terminal Domain Of Tim23mentioning
confidence: 99%
“…6a). Surprisingly, it has been reported that Tim23 is integrated into the outer membrane through its N-terminal domain 25 . Therefore, we investigated which domain of Tim23 forms the cation-selective channel identified here.…”
Section: Channel Formation By the C-terminal Domain Of Tim23mentioning
confidence: 99%
“…The TIM23 complex translocates preproteins with cleavable N -terminal presequences into the matrix or inner membrane, whereas the TIM22 complex is used by a subset of inner membrane proteins with internal import signals (5,68). Transfer of preproteins through both mitochondrial membranes occur at socalled translocation contact sites at which the outer and the inner boundary membrane come in close contact (69)(70)(71)(72). These translocation contact sites are formed on demand in a dynamic fashion between TOM and TIM23 or TIM22 complexes during the translocation of preproteins into the matrix or inner membrane ( Fig.…”
Section: Translocation Across the Inner Membranementioning
confidence: 99%
“…These translocation contact sites are formed on demand in a dynamic fashion between TOM and TIM23 or TIM22 complexes during the translocation of preproteins into the matrix or inner membrane ( Fig. 1) (71,(73)(74)(75)(76). Arrest of a matrix-targeted preprotein in such a way that it spans tightly both outer and inner membranes can form a stabilized translocation contact site.…”
Section: Translocation Across the Inner Membranementioning
confidence: 99%
See 2 more Smart Citations